The Role of Non-Agricultural Rural Activities in the Transformation of Rural Areas in Kediri Regency - Isnaini Nur Husna (The Indonesian Journal of Planning and Development, 2023)
Rural-to-urban transformation is marked by increasing population movement and a shift from agricultural to non-agricultural sectors. This transformation reflects the impact of urbanization on rural areas, resulting in economic diversification and job pluralism. Non-agricultural rural activities provide alternative income sources, especially for households with limited or no agricultural land, contributing to labor absorption, economic growth, and poverty reduction. Kediri Regency in East Java exemplifies this phenomenon, with 29 villages reclassified as urban according to the Central Bureau of Statistic Regulation No.37 of 2010. This study aims to analyze non-agricultural rural activities in the context of rural transformation in Kediri Regency. It examines external and internal driving factors as well as the outcomes of such activities. A quantitative approach was used, including descriptive statistical analysis and Geographic Information Systems (GIS). A scoring method identified the most influential drivers and outcomes. The study used multistage sampling area and snowball techniques focusing on non-agricultural households in three villages: Bringin, Gempolan, and Petok, each with varying proximity to primary and secondary cities. Findings show that proximity to urban centers is the main external driver in Bringin, while physical capital dominates in Gempolan and Petok. Internally, innovation drives non-agricultural activities in Bringin and Petok, whereas access to credit is more influential in Gempolan. Income improvement is the most reported outcome across all villages. The research concludes with policy recommendations to support rural development programs aligned with the most significant influencing factors, fostering diversification and sustainable rural transformation.